Reference Blood Chemistry Values Throughout the Lifespan of M. spretus - Coviello-Mclaughlin, Gina M.; Prowse, Karen R. (Contemporary topics in laboratory animal science, 1999)
In the present study, blood chemistry values for Mus spretus are reported and analyzed with respect to age and gender. Cholesterol values differ significantly (P = 0.01) between young (2 to 6 months) and aged (25 to 31 months) M. spretus, and direct or conjugated bilirubin values differ significantly (P = 0.01) between male and female animals. These findings indicate that cholesterol concentrations in M. spretus change with age and that direct bilirubin values differ depending on gender.